(untitled) (Global Journal of Medical Research, 2023)
This study aimed to evaluate antihyperglycemic and antioxidant activities of an herbal medicinal product codified "DD3". From dry aqueous extract, the differents tests were carried out. Phytochemical screening showed presence of alkaloids, polyphenols, flavonoids, saponosides, sterols and terpens. Regarding antioxidant activities, DPPH test showed that DD3 remedy (IC50= 59.39 ± 0.69 µg/mL) had a lower antioxidant potential than vitamin C (IC50= 7.93 ± 0.45 µg/ mL), and that was identical for ABTS test for which IC50 = 94.34 ± 0.73 µg/mL for the Remedy against IC50= 25.87 ± 0.46 µg/mL for Gallic acid. About antihyperglycaemic test, unlike glibenclamide which induced hypoglycaemia after 3 hours, the remedy at 500 mg/kg bw brings blood sugar levels back to normal values after this time. The DD3 remedy could be used as a blood sugar regulator.